Tools of the Ethylene Trade: A Chemical Kit to Influence Ethylene Responses in Plants and Its Use in Agriculture. Issue 8 (28th August 2019) - Depaepe, Thomas; Van Der Straeten, Dominique
Abstract: The simplest unsaturated hydrocarbon, ethylene or ethene, is one of the most widely produced organic chemicals worldwide. It serves as a building block for various materials and chemicals, including plastics, ethanol, detergents, and many more. Strikingly, it also acts as a signaling molecule in virtually all physiological processes and during all developmental stages in plant life. Plant biologists consider ethylene to have a tripartite role in plant development; this gaseous molecule can serve as a plant growth regulator, an aging hormone, and as a stress controller, aiding in defense against both biotic and abiotic stressors. Therefore, the regulation of the ethylene status is indispensable in both agricultural and horticultural practices. Since its discovery as a phytohormone, many chemicals have been developed that are able to affect ethylene responses in plants. Here, an extensive overview of the current toolbox of ethylene regulators, their discovery, function, and applications in both the agri‐ and horticultural field is presented. Furthermore, possibilities and considerations related to novel small molecules, such as those emerging from the chemical genetics field, are discussed. Abstract : Ethylene is a phytohormone indispensable for plant development. Here, the currently available toolkit of small molecules affecting ethylene responses is discussed. An overview of their discovery, structure, and mode of action is presented, especially in light of their use in both research and agri‐ and horticulture. In addition, possibilities for discovery of novel agonists and antagonists are described.